Different diameters of titanium dioxide nanotubes modulate Saos-2 osteoblast-like cell adhesion and osteogenic differentiation and nanomechanical properties of the surface. Issue 20 (11th April 2019) - Voltrova, Barbora; Hybasek, Vojtech; Blahnova, Veronika; Sepitka, Josef; Lukasova, Vera; Vocetkova, Karolina; Sovkova, Vera; Matejka, Roman; Fojt, Jaroslav; Joska, Ludek; Daniel, Matej; Filova, Eva
Abstract : Nanostructured cpTi surfaces affected Saos-2 cell adhesion, proliferation, and osteogenic differentiation as well as the nanomechanical properties of the surface. Abstract : The formation of nanostructures on titanium implant surfaces is a promising strategy to modulate cell adhesion and differentiation, which are crucial for future application in bone regeneration. The aim of this study was to investigate how the nanotube diameter and/or nanomechanical properties alter human osteoblast like cell (Saos-2) adhesion, growth and osteogenic differentiation in vitro . Nanotubes, with diameters ranging from 24 to 66 nm, were fabricated on a commercially pure titanium (cpTi) surface using anodic oxidation with selected end potentials of 10 V, 15 V and 20 V. The cell response was studied in vitro on untreated and nanostructured samples using a measurement of metabolic activity, cell proliferation, alkaline phosphatase activity and qRT-PCR, which was used for the evaluation of osteogenic marker expression (collagen type I, osteocalcin, RunX2). Early cell adhesion was investigated using SEM and ELISA. Adhesive molecules (vinculin, talin), collagen and osteocalcin were also visualized using confocal microscopy. Moreover, the reduced elastic modulus and indentation hardness of nanotubes were assessed using a TriboIndenter™. Smooth and nanostructured cpTi both supported cell adhesion, proliferation and bone-specific mRNA expression. The nanotubes enhanced collagen type I and osteocalcin synthesis, compared to untreated cpTi, and the highest synthesis was observed on samples modified with 20 V nanotubes. Significant differences were found in the cell adhesion, where the vinculin and talin showed a dot-like distribution. Both the lowest reduced elastic modulus and indentation hardness were assessed from 20 V samples. The nanotubes of mainly 20 V samples showed a high potential for their use in bone implantation.